Increasing responsibility, initiative and learning motivation in students - Najmutdinova , Gulnozakhon Bakhtiyorovna (The Lingua Spectrum, 2026)
This article explores the psychological and pedagogical foundations for developing responsibility, initiative, and learning motivation among students. In modern education, the learner’s active participation, independent thinking ability, and responsible attitude toward academic tasks are considered key factors in achieving high learning outcomes. The study analyzes internal and external sources of motivation, strategies for creating a positive learning environment, and methods for encouraging student initiative and strengthening their sense of responsibility. In addition, the role of teacher–student collaboration, effective feedback, and the importance of independent learning assignments are examined. The findings indicate that enhancing students’ motivation significantly contributes to improving the overall quality of education and fostering personal growth.